TOOLS OF SOCIAL SERVICES IN THE COLLABORATIVE TRAINING OF FUTURE TEACHERS OF PRIMARY SCHOOL - Kuchakovska, Halyna (Educological discourse, 2018)
The article reveals the essence of the use of social services tools during collaborative training of future teachers of primary school; briefly describe the possibilities of using social services tools during the organization of a collaborative occupation. The subject of the research is the instruments of social services in the process of collaborative training future teachers of primary school. The object of research is the process of training future teachers of primary school. When working on the article used the following methods: analysis of scientific and pedagogical and methodological literature on the issues of the article; comparison, study and generalization of pedagogical experience in improving the training process in the system of vocational training. According to the results of the study, it was found that the introduction of new methods and techniques, in particular, collaborative learning with the use of social services tools into the learning process, will increase the motivation for future teachers of primary school training, will promote autonomy and responsibility in terms of solving certain tasks in the group, develop teamwork skills, responsibility, prognosticity of thinking and creative approach to problem solving.